Political and Cultural Boundaries in the Conflict between Indonesia and China in the South China Sea - Khoirur Rizal Lutfi (Faculty of Law Universitas Lampung, 2023)
China's unilateral claim to an area in the South China Sea, which it calls the nine-dash line, the traditional fishing ground, has triggered boundary conflicts in border countries. In this context, Indonesia calls the area that intersects the North Natuna Sea based on the 1982 United Nations Convention on the Law of the Sea (UNCLOS). This difference in perception is alarming to the international relations between the two countries. This paper aims to analyze how international law views the position of political and cultural boundaries as the basis for claims to an area. This way, dispute resolution with a win-win solution perspective can be formulated in the South China Sea case. The analysis results show that political and cultural boundaries have justification and legitimacy based on international law. Political boundaries emphasize the State's commitment to translating agreements into international treaties bilaterally, regionally, or universally. In contrast, cultural boundaries still require an inventory of the evidence that China's claim is based on, whose legitimacy process must be based on a decision-making institution. However, any legal process will be challenging if the cultural approach is not completed. Apart from that, the essential thing in resolving the South China Sea conflict is the commitment of the State's compliance to international agreements made, decisions of dispute resolution institutions, and settlement steps through a cultural approach.